Rational or altruistic: the impact of social media information exposure on Chinese youth’s willingness to donate blood - Zhang, Zhijian; Liu, Qilong (Frontiers in Public Health, 2024)
As the amount of blood used in China's medical institutions increases, there currently exists the problems of insufficient blood in blood banks and shortage of blood supply, how to call on more potential donors to participate in blood donation is a major problem that needs to be solved by medical institutions at present. Currently, social media has become the main way for Chinese youth groups to obtain information, and related blood donation information on social media can influence the attitudes and beliefs of youth groups about blood donation. Based on this, we conducted a survey with 455 participants to investigate the relationship between exposure to blood donation information on social media and youth's willingness to donate blood, and constructed structural equations based on the Theory of Reasoned Action (TRA). The results showed that exposure to blood donation information on social media, self-efficacy, and altruism were positively associated with young people's willingness to donate blood, suggesting that relevant measures could be strengthened to increase young people's willingness to donate blood.